Does the National Health Insurance Program Affect Life Insurance Demand in Indonesia? - Rapi, Kristio; Priyarsono, Dominicus Savio; Jahroh, Siti; Bakhtiar, Toni (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2026)
Research Originality: This research pioneers a macro-institutional approach to life insurance demand by empirically proving a definitive crowding-out effect induced by Indonesia's universal healthcare mandate. Research objectives: To investigate the dynamic impact of the state-mandated JKN program and national income on private LID in Indonesia. Research methods: This study utilizes a Vector Error Correction Model (VECM) and structural break analysis on annual data from 2002 to 2022 to rigorously capture regime shifts, short-run frictions, and long-run equilibria. Empirical result: The findings reveal a definitive crowding-out effect: the JKN mandate and rising compulsory insurance penetration significantly depress private LID, whereas income maintains a significant positive elasticity in the long run. Furthermore, structural break tests confirm a fundamental, permanent shift in consumer purchasing behavior post-2014, coinciding with the introduction of the JKN program. Implications: Policymakers must orchestrate a regulatory environment that protects universal healthcare while actively sustaining the development of the private life insurance market. Insurers must innovate beyond state-overlapping benefits by developing investment-linked products and optimizing Coordination of Benefits (CoB) frameworks. JEL Classification: D12, G22, G28, I13, I18